Consistency and Law Comparison in Consumer Protection Law Design in the Light of the Socially Responsible Market Economy Approach - Stefan Koos (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Social justice is an essential issue in the development of Indonesian law of the 21st century. Consumer protection is an aspect of social justice because it maintains